Plant traits and environment affect the contents of medicinal components in Ziziphi spinosae semen in Lincheng County of Hebei Province - Liu, Qianyuan; Chen, Yaxuan; Xue, Zijing; Chen, Yanmei; Jiang, Jianming (BMC plant biology, 2025)
Ziziphi Spinosae Semen (ZSS) is used in the treatment of insomnia in traditional Chinese medicine. However, the underlying drivers of the contents of medicinal components in ZSS are inadequately understood. In this study, samples of the roots, leaves, and fruits of Ziziphus jujuba were collected from 24 habitats. The contents of four medicinal components, ten leaf traits, eight root traits, and nine soil characteristics were then analyzed. The contents of jujuboside A, jujuboside B, spinosin, and 6'''-feruloyl spinosin of ZSS in Lincheng were 0.52-4.41, 0.22-0.87, 0.53-1.89, and 0.25-0.80 mg·g.sup.-1, respectively. The contents of jujuboside A, spinosin, and 6'''-feruloyl spinosin increased with increasing altitude at a range of 60-500 m. Environmental factors, plant traits and their combined effects explained 16.06%, 14.24% and 39.68% of the contents of medicinal components in ZSS, respectively. Among environmental factors, soil total potassium and phosphorus had a greater impact on the contents of medicinal components in ZSS, in contrast to soil total organic carbon and nitrogen. Among plant traits, root total carbon, specific root length, leaf total carbon, the photosynthetic parameter, and water use efficiency were the main contributors to changes in the contents of medicinal components in ZSS. Therefore, management methods of jujube cultivation need to adjust based on the characteristics of soils and local environmental factors. These results can provide a basis for predicting the quality of medicinal components of ZSS by measuring easily obtained plant functional traits.